(untitled) (LEARNing Landscapes, 2016)
Two educators explore issues related to arts-based education and assessment. Our students are being short-changed, we believe, when they are not given opportunities to appreciate the arts, to value the richness they bring to our lives and an understanding of the world. We believe that education needs to rebalance the ways in which children spend their time, how they are assessed, and what is valued. We also believe that deepening our understanding and awareness of how we value and assess the arts will deepen and strengthen the way we understand and value all types of knowledge and interactions in the world.